Economic 'miracles' : studies in the resurgence of the French, German, and Italian economies since the Second World War - Hennessy, Jossleyn; Lutz, Vera C.; Scimone, Giuseppe; Institute of Economic Affairs (Great Britain) ([London] : Published for the Institute of Economic Affairs by A. Deutsch, 1964)
The book discusses the experience of the three countries in Europe- Germany, France and Italy in economic development that can only be described as a miracle.
Includes index
"Bibliographies": p. 221-224.
usc 25/01/2019
Loans
Keywords: Germany (West); Italy; France